A review on Nitinol shape memory alloy heat engines - Abubakar, Rabiu Ahmad; Wang, Fan; Wang, Linxiang (Smart materials and structures, 2021)
Nitinol (NiTi) shape memory alloy (SMA) heat engine is a very promising candidate application of SMA since its invention, but yet to be put as commercial due to its low efficiency and performance. In this paper, a review of different types of NiTi SMA heat engine is presented. The review is done based on the following headings: conceptual design, constitutive driving model, the performance of the engine, and engine limitations. Factors like temperature, cooling rate, size of NiTi SMA element, and the stretch ratio of NiTi SMA spring were identified as determinants of final output power and efficiency of SMA heat engines. It is found that a crankshaft NiTi SMA heat engine produced the highest power output value of 4 watt, an unsynchronized pulley NiTi SMA heat engine with 11.3% of engine efficiency has the highest engine performance so far recorded. Some engine's drawbacks like an improper driving model, drag loss, backsliding were identified as the major problem affecting the engine performance, and which, if solved, will increase the overall performance and efficiency for future development toward its commercialization.